Simulated Herbivory Weakens Plant-Soil Feedbacks in Competitive Mixtures of Native and Invasive Woodland Plants - Bennett, Savannah I.; Howard, Chelsea; Albrecht, Renee; Smith-Ramesh, Lauren M.; Reynolds, Heather (Frontiers in Ecology and Evolution, 2020)
Plant-soil feedback (PSF), the process by which plants influence con- or heterospecifics via alteration of abiotic or biotic soil properties, is a known driver of plant coexistence and invasion. Yet there is limited understanding of how PSF interacts with other important drivers of plant community structure and dynamics, such as aboveground herbivory. Aboveground herbivory and PSFs are ubiquitous processes in plant communities, but traditional PSF experiments in the greenhouse eliminate herbivory as an experimental factor. Aboveground herbivory can affect plant-soil systems in multiple ways and therefore is likely to strongly interact with PSF. Herbivores can be selective, preferring certain species over others, which could influence PSF dynamics. Aboveground herbivory could also affect PSF dynamics by influencing photosynthate allocation, defense compound production, and soil nutrient levels. An existing conceptual framework predicts that aboveground herbivory should generally weaken pathogen-, mutualist- and soil nutrient-driven feedbacks, and a logical extension of these predictions is that aboveground herbivory will weaken PSF as a driver of plant species invasion. Using a Midwest urban woodland study system, we first measured aboveground mammalian herbivore pressure on native woodland perennials used in local restoration efforts. We then simulated these levels of herbivory in a greenhouse experiment to assess whether and how aboveground herbivory alters net pairwise PSF interactions between these native species and Euonymus fortunei, a common invasive plant of Midwest urban woodlands. Results support predictions that aboveground herbivory weakens PSF interactions. In our experiment, simulated herbivory eliminated PSF among E. fortunei and a co-occurring community of native species, although this effect depended on competitive context. When the native community and the invasive species were grown separately, net feedback was neutral regardless of herbivory, but when grown in a competitive mixture, feedback between the native community and the invader switched from negative to neutral when herbivory was imposed. To assess the generality of these findings, future studies are needed that examine herbivory-PSF interactions across multiple native-native and native-invasive species combinations, and for a range of plant community types.